The Ratio of Bax And Bcl-2 in the Cerebrum of Newborn Rattus Novergius Given Mackerel Oil During Pregnancy - Mikra Latisfian; Widjiati Widjiati; Hermanto Tri Joewono; Siti Nur Kholifah; Ali Medina (Jurnal Kebidanan, 2023)
The quality of a nation is determined by nutritional intake during pregnancy. Pregnancy is the right time to prepare the brain's potential optimally, one of which is the intake of mackerel oil which is rich in omega-3. Omega-3 fatty acids can stimulate gene expression and nerve activity, increase synaptogenesis and neurogenesis, and prevent apoptosis. This study aims to analyze the intake of mackerel oil during pregnancy to the ratio of Bcl-2 / Bax in the cerebrum. This research is a true experiment with a posttest-only control group design. 30 pregnant Rattus norvegicus mothers aged 2-3 months were divided into 3 groups, namely the control group (K), the mackerel fish oil group (P1), and the omega-3 supplement group (P2). This research was conducted at the Experimental Animal Cages and Pathology Laboratory, Faculty of Veterinary Medicine, Airlangga University. The mean Bcl-2 / Bax cerebrum ratio was 1.127 ± 0.342 (K), 3.928 ± 1.984 (P1), and 2.526 ± 1.122 (P2). The ANOVA test on the Bcl-2 / Bax ratio in the cerebrum showed a significant difference with a p-value of 0.000. The Bcl-2 / Bax ratio in the cerebrum of Rattus norvegicus newborns treated with mackerel oil on Rattus norvegicus mothers during pregnancy showed higher results than the other groups.